Evaluation of Indigenous Cuisine in Hotels and Restaurants in Aba, Abia State, Nigeria - Aji, Rosemary Uloma; Okoro, Enyinnaya Okoro; Managwu, Lilian Chinenye (Archives of Current Research International, 2019)
As a result of the economic and social contribution of hospitality and tourism industry, there is a strong competition all over the world for the indigenous cuisine of the area. Most people are attracted to a specific area based on the cuisine. The aim of this study is to identify the major indigenous cuisine serve in Hotels and restaurant in Aba, since indigenous cuisine attracts tourists. Twenty (20) selected hotels were used for the study. Data for the study were collected using questionnaire and oral interviews. Descriptive statistics and simple percentage were used for the study. The result obtained shows that most hotels in Aba serve mainly continental cuisine more than the indigenous cuisine. Therefore the need to encourage branding of indigenous cuisine since it boosts our local economy, attracts tourists and our cuisine is more nourishing than the continental cuisine.